LOCAL WISDOM OF URBAN MUSLIMS IN INHERITANCE DISTRIBUTION - Rasidin Barasa; Asmuni Asmuni; M. Jamil; Syafaruddin Syafaruddin; Vasco Fronzoni (Akademika : Jurnal Pemikiran Islam, 2023)
This research aimed to explain the local wisdom of Medan urban communities in the distribution of inheritance. In urban communities, when inheritance is divided, it sometimes creates hostility between families due to inheritance issues between the father's brothers when dealing with daughters, which often results in differences in the amount of inheritance obtained. This study was field research, while the approach used is sociology and legal anthropology. Data collection techniques used in this study were interviews and documentation. An important finding in this research is that the urban Muslim community in Medan City has its own concept, local wisdom, in solving the division of inheritance between daughters when dealing with their father’s brothers. The local wisdom of urban Muslims in the city of Medan shows that there is a special legal formula as a third way of resolving problems, which is not only considered to have met the values of justice but also following the values of the common good, namely by continuing to give a share of the dead inheritance to the father’s brother by dead daughters through the path of sadaqah (which in this case researchers call it "sadaqah wajibah") because if it is not given it will result in disharmonious familial relations between the dead family and their siblings, and of course, as with shadaqah in general, the gift of inheritance from dead to his brothers based on the values of propriety and sincerity.